Projeto de extensão universitária em orientação profissional (OP) para jovens: uma parceria entre universidade e instituição formadora de aprendizes - Sousa, Rosemberg Jônatas Gomes de [UNESP]; Feijó, Marianne Ramos [UNESP]; Camargo, Mario Lázaro [UNESP]; Campos, Dinael Correa de [UNESP]; Goulart Júnior, Edward [UNESP]; Cardoso, Hugo Ferrari [UNESP] (My University, 2014)
Work is one of the fundamental elements for building the human identity. In this way, the Career Guidance (CG), whose character is reflective, increases choice processes, and can favour further relations from students to work. This article treated about university extension actions guided to four groups of young apprentices, whose families have low scholarity and income. Besides the synthesis of the objectives and methods of the project, they were transcripted students' narratives about the benefits they achieved, and the conclusions of Psychology students who were envolved. The qualitative comprehension of those data allowed to consider that the CG activities widened the self-knowledge, the choice and development possibilities of the participants. It is suggested the expansion of these practices.

O trabalho é um dos elementos fundamentais na construção da identidade humana. Nesse sentido, a Orientação Profissional (OP), de caráter reflexivo, incrementa processos de escolhas, podendo favorecer relações futuras dos orientandos com o trabalho. Tratou-se neste artigo de ações de extensão universitária voltadas para quatro grupos de jovens aprendizes, cujas famílias têm baixa escolaridade e renda. Além da síntese de objetivos e métodos do projeto, foram transcritas narrativas dos orientandos sobre benefícios alcançados, e conclusões de estudantes de Psicologia envolvidos. A compreensão qualitativa das mesmas possibilitou considerar que as atividades de OP ampliaram o conhecimento e as possibilidades de escolha e de desenvolvimento dos participantes. Sugere-se que essas práticas sejam expandidas.
University extension project of career guidance (CG) for Youth: a partnership between University and an Institution for Apprentices Education
Keywords: Apprentices; Career Guidance; Work; Aprendiz; Orientação Profissional; Jovens